The Effect of Economic Reforms of 1980s and of the Customs Union 1996 upon the Turkish Intra-Industry Trade - Sule Akkoyunlu; Konstantin Arkadievich Kholodilin; Boriss Siliverstovs (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In this paper we analyze the impact of the economic reforms implemented in 1980s and of the Custom Union Agreement of 1996 on the intra-industry trade in Turkey. Using the panel data for 15 trading partners of Turkey and the sample period 1970-2005, we record the positive impact of both reforms with the former reforms exercising stronger influence on the intra-industry trade measured either by the Grubel-Lloyd or the Brulhart?s indices. We also control for other factors like economic size, difference in income per capita and in economic size between Turkey and its trading partners in our empirical regressions.
Keywords: F14; C23; 330; Intra-industry trade; Customs Union Agreement; panel data estimation